Measurement of the relative branching ratio of B-s(0) -> J/psi f(0)(980) to B-s(0) -> J/psi phi - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Scanlon, T.; et al. (Amer Physical Soc, 2012)
We present a measurement of the relative branching fraction, R-f0/phi, of B-s(0) -> J/psi f(0)(980), with f(0)(980) -> pi(+)pi(-), to the process B-s(0) -> J/psi phi, with phi -> K+K-. The J/psi f(0)(980) final state corresponds to a CP-odd eigenstate of B-s(0) that could be of interest in future studies of CP violation. Using 8 fb(-1) of data recorded with the D0 detector at the Fermilab Tevatron Collider, we find R-f0/phi = 0.275 +/- 0.041(stat) +/- 0.061(syst).